Secagem e caracterização de polpa de tamarindo (Tamarindus indicos L.) em cast-tape dryer e estufa convectiva - Tachiua, Iolanda Nhacha Daniel (2024)
Studies on drying fruit and vegetables have grown considerably as a method of preserving food, reducing the moisture and water activity of these products to levels that hinder microbial growth and the development of physic-chemical reactions while preserving nutrients. This study aimed to evaluate tamarind pulp and foam layer drying by a cast-tape dryer (CTD) and in an oven. To achieve the objective, this study was divided into three parts: the first consisted of a literature review on drying tamarind fruit (pulp, seeds, and peel) by different methods. This review looked at the main drying processes, tamarind pulp and residues' nutritional and/or bioactive properties, and their application in different areas. The main methods studied were drying in air circulation ovens, spray drying, freeze-drying, foam-mat, drum drying, and osmotic dehydration. In the second part of this work, tamarind pulp was characterized by its nature, and several drying experiments were carried out to study its kinetics by CTD. These experiments used different drying temperatures (60, 75, and 90°C) and tamarind pulp layer thicknesses (2, 3, and 4 mm). The results showed that after 8 hours of tamarind pulp drying kinetics at temperatures of 60 and 75°C and the lowest thickness (2mm), the samples moisture stabilized at 24%. At 90°C and a thickness of 2mm, stability occurred at 15% moisture. It was not possible to obtain a powdered product as expected, which demonstrated the technological difficulty of drying the pulp without the aid of additives. The third part studied the drying and characterization of tamarind pulp foam with the addition of maltodextrin and Arabic gum, using two drying temperatures (75 and 90°C) and two drying methods (CTD and oven) to produce tamarind pulp powder. The results showed that using the foaming agent and additives significantly reduced the drying time, and the powders produced had moistures ranging from 10,30±0,18 to 13,27±0,05%, which is acceptable for this type of product. The tamarind pulp powder was characterized by its water activity, colour, hygroscopicity, pH, bulk density, and bioactive compounds (phenolic compounds, flavonoids, ascorbic acid, and titratable acidity). The results allow us to conclude that it was possible to obtain tamarind pulp powder by applying a foam-mat and adding maltodextrin and Arabic gum.